2007
DOI: 10.1007/s00417-007-0536-2
|View full text |Cite
|
Sign up to set email alerts
|

Retinal pigment epithelial tear following intravitreal ranibizumab injections for neovascular age-related macular degeneration

Abstract: As with other anti-vascular endothelial growth factor treatment for CNV, RPE tear might occur after intravitreal ranibizumab injection even after previous uneventful intravitreal injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22] As the acute visual consequences are only limited after a RPE tear has been initiated, a good visual prognosis was often presumed for this complication, which is in agreement with our findings. However, with longer follow-up this prognosis decreased significantly, with a mean loss in BCVA deterioration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22] As the acute visual consequences are only limited after a RPE tear has been initiated, a good visual prognosis was often presumed for this complication, which is in agreement with our findings. However, with longer follow-up this prognosis decreased significantly, with a mean loss in BCVA deterioration.…”
Section: Discussionsupporting
confidence: 89%
“…[15][16][17][18][19][20][21][22] However, little is known about the long-term outcome in these patients. The aim of the present study, therefore, was to evaluate the long-term visual and morphologic prognosis after RPE tears in association with anti-VEGF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, patients with RPE tears who received additional anti-VEGF therapy were followed for a mean of 52 months (range, 36-72 months), much longer than reported previously. [6][7][8]10,12,14 We observed that the final visual outcomes were not as devastating as reported previously. 1,3,7,[9][10][11][12][13] Immediately after the tear develops, there is a sudden decrease in vision accompanied by intense metamorphopsia.…”
Section: Discussionsupporting
confidence: 71%
“…[1][2][3][4][5][6][7][8] Two studies have reported identical rates of RPE tears of 17% in eyes with a PED and neovascular age-related macular degeneration that had received anti-VEGF therapy. 15,16 Rapid contraction of the choroidal vascular membrane beneath a serous RPE detachment is believed to be the underlying cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation